Troponin T and coronary angiography findings in patient with unstable angina pectoris - Karaca, I; Akbulut, M; Kilicoglu, AE; Ilkay, E; Pekdemir, M; Arslan, N (Medimond S R L, 2001)
In unstable angina pectoris (UAP) elevation in serum troponin T level is an indicator of poor prognosis. In this study distinctions in coronary anatomy in patients with UAP whose serum cTnT levels elevated or not were compared. 90 patients with Braunwald class III angina were included. Serum troponin T measurements were done in 2, 6, 12, 18 and 24th hours. Coronary angiography was applied to all patients before discharge. Clinical course was followed for 4.4+/-1 months. 3 vessels disease n=18 ( 25.7 %); n=10 (50 %) p<0.001, thrombus appearance n=4 (5.7 %); n=5 (25 %) p=0.005 and severe stenosis in vessel responsible for clinic n=45 (64.3 %); n=18 (90 %) p<0.004 were detected.
4th International Congress on Coronary Artery Disease -- OCT 21-24, 2001 -- PRAGUE, CZECH REPUBLIC
Keywords: Artery Disease; Benefit; Risk